Kriminalisasi Nilai Moral: Konstruksi Kebijakan Kriminal di Negara Muslim Modern - Kadir, Zul Khaidir Kadir (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Criminalization of moral values refers to the legalization of prohibitions on behavior that is considered contrary to religious, ethical, or customary norms, although it does not always involve direct violations of the rights or interests of others. Unfortunately, the establishment of criminal policies based on moral values is often considered an expression of national identity based on religion, but in practice it often triggers heated debates about legal legitimacy, social justice, and violations of individual rights. This study aims to critically analyze the phenomenon of criminalization of moral values in criminal policies in modern Muslim countries. In addition, it focuses on identifying the main elements that form criminal policies based on morality, evaluating their impact on social justice and human rights, and proposing an alternative framework that aims to create harmony between religious norms and universal values. This study uses a normative legal research method using a comparative approach. The data collection method is collected using library research, then analyzed qualitatively and presented descriptively. The results of the study show that the criminalization of moral values in the criminal policies of modern Muslim countries creates a dilemma between religious norms and legal needs that are relevant to social reality, often causing injustice and repressive social control. To overcome this, an inclusive approach is needed, such as proportionality, restorative justice, and community participation, in order to create harmony between religious morality, substantive justice, and the needs of modern society, while strengthening legal legitimacy and social cohesion.